Time‐Dependent Density Functional Theory, AIM Analysis, NLO, and Thermodynamic Properties of Propofol and Adsorption Effects of Propofol Drug over Carbon Nanotube (C56H16) as the Factor of Drug Delivery System. Issue 1 (23rd February 2023) - Dwivedi, Apoorva; Narayan, Vijay; Singh, Vijay; Singh, Vinod Kumar; Pandey, Anoop Kumar
Abstract: This article presents a comprehensive quantum chemical study of the Propofol molecule using the Density Functional Theory (DFT). The UV (Ultra Violet)plots, Non‐Linear Optical (NLO) properties' calculations, and Density Of State (DOS) plots are studied with the help of DFT using 6–311G (d, p) as the basis set. Quantum Theory of Atoms in Molecules (QTAIM) analysis shows weak intramolecular interactions of CH….O. The NLO calculations show that the molecule is a good candidate as a future nonlinear optical material. The parameters of NLO Propofol and Propofol (CH2)n, n = 1–5 are also calculated with the same level theory. During this study, we have mainly focused on the profile of its electronic properties, the vital vibrational modes during movement in the isolated gas phase, and a better understanding of the unbound interaction between drug propofol and carbon nanotubes [C56H16].